A Review on Development of Aerobic Granular Sludge Membrane Bioreactor for the Industrial Effluent Treatment - Ingale, Rakshanda M; Thorat, Sanjaykumar R (Asian Journal of Biological and Life Sciences)
The technology of aerobic granular sludge and Membrane Bioreactor (MBR) were combined to develop an Aerobic Granular Sludge Membrane Bioreactor (AGMBR). Biomass content is high, higher the retention time of biomass, and the capacity of phosphorus and nitrogen removal has been shown by aerobic granular sludge; now a day it is a promising option for wastewater treatment. Reclaiming wastewater one of the favourite choices is Membrane technology in removing organic and inorganic impurities they have recognised as moderately operative with biological entities removal from wastewater. Consequently, the wastewater treatment membrane bioreactor and aerobic granular sludge technology are dynamic and new trending cost-efficient technologies. This article aims to review all the potential applications and principles in AGMBR technology.
Keywords: Aerobic granular sludge; AGMBR; Cost-efficient; industrial wastewater; Membrane bioreactor; Membrane fouling